Flexitime and employee happiness at workplace: A quantitative study of software houses - Madiha Kiran; Sobia Khurram (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
Employee happiness is an emerging concept that has been incorporated with internal workplace flexibility or flexitime. The aim of this study is to find out the relationship of internal workplace flexibility with employee happiness. Employee happiness at the workplace has been studied through the lens of three components, including affective organizational commitment, employee engagement and job satisfaction. These constructs have been studied collectively to acquire a comprehensive understanding regarding their relationships, outcomes and influences on one another. For this study, data have been collected from ten registered software houses of Lahore, Pakistan, through self-administrated questionnaire, 358 participants participated in the survey. Non-parametric analysis of the data shows that flexitime has a positive relationship with affective organizational commitment, employee engagement, job satisfaction and thus employee happiness. Thus it can be concluded that when organizations give discretion to its employees to decide about when, where, what and how to work, it makes employees more committed, engaged, satisfied and thus happier.
Keywords: 330; Flexitime; employee happiness; affective organizational commitment; employee engagement; job satisfaction